Fluorine Substitution in Diamine Covalent Organic Frameworks: Computational Analysis of CO2/N2 Adsorption and Permeability - Darmawan, Noviyan; Apriliyanto, Yusuf Bramastya; Jati, Andreas Ary Chrisna; Kusumawardani, Cahyorini (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
In this study, we investigated the effect of fluorine substitution on a previously reported diamine based covalent organic framework (COF), designated as IPB-2H. A new fluorinated analogue namely IPB-2F2 was modeled and its adsorption and permeability characteristics for CO2/N2 gas mixtures were evaluated through computational analysis. Ab initio structural optimization results showed that the reduced pore size of IPB-2F2 compared to IPB-2H was attributed to the larger atomic size and higher electronegativity of fluorine compared to hydrogen atom. Molecular dynamics (MD) simulations demonstrated that IPB-2F2 exhibited lower permeation rates for CO2 and N2 than its non fluorinated counterpart; indicating that fluorine atoms effectively reduced gas permeation. Adsorption isotherms revealed enhanced adsorption capacities for IPB-2F2, with increased CO2 affinity resulting from strong van der Waals interactions. Selectivity analyses showed that IPB-2F2 preferentially absorbed CO2 over N2, with selectivity values consistently greater than 1. The enhanced gas uptake capacity and hydrophobicity of IPB-2F2 highlighted its potential for industrial applications as a post-combustion CO2 capture material.